Effects of Vitamin B-Complex Supplementation Alone or Combined with Estrogen on Bone Loss in Ovariectomized Rats - Al-Saeed, Hanan; Ibrahim, Bassant; Shalby, Aziza (Journal of medical and pharmaceutical sciences, 2017)
Background: Postmenopausal osteoporosis has become a global health issues recently. Several vitamins play a role in building and maintenance of bones. Objective: To evaluate the possible roles of vitamin B-complex supplementation alone or combined with estrogen in the improvement of osteoporosis in ovariectomized (OVX) rats. Materials and Methods: Fifty adult female albino rats were equally divided into 5 groups then 4 groups were exposed to ovariectomy: Control group, OVX group, OVX/ Ethinyl estradiol (EE) group, OVX/B-complex group and OVX/EE/B-complex only. All treatments were started 4 weeks after surgery and continued for 8 weeks. Blood samples were collected to measure serum levels of homocysteine (HCY), bone–specific alkaline phosphatase (BAP), collagen type 1 cross-linked C-telopeptide (CTX) and calcium (Ca++). Results: Ovariectomy increased serum levels of Ca++, bone turnover markers (BAP and CTX) and homocysteine (HCY). Serum Ca++ levels were increased, while serum levels of bone markers and HCY were decreased) in all treated groups but, only rats treated with EE and vitamin B-complex returned the serum levels of CTX and HCY to normal. Conclusion: Vitamin B-complex showed some antiosteoporotic effects in OVX rats.